Edukasi Literasi Bahasa dan Teknologi pada Anak Usia Dini di Yayasan Aku Melihat Engkau (AME) Medan - Irving Josafat Alexander; Hersakso Sinurat; Gloria Sirait; Monalisa Marta Siahaan; Ramlan Silaban; Justinos Ray Nainggolan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The focus of this service activity is to develop language literacy skills from an early age through presentation of material and short videos combining listening and speaking communication as well as technological literacy skills to increase children's knowledge of the impact of technology. The location of this service activity was carried out at the Aku See You (AME) Foundation in Medan. Participants who took part in this activity were 20 children aged 7-15 years who were at the AME Foundation. The details of the form of outreach activities are: First, a short material presentation that introduces the importance of language literacy and technological literacy, a short interactive video presentation about the positive and negative impacts of technology. A short story about Controlling Yourself from the Negative Impact of Technology and a Closing Session in the form of an educational game with a technology theme with the aim of building solidarity between children at the AME Foundation. Based on the results of the service activities, very high enthusiasm was obtained from the service participants as indicated by the many questions asked by the service participants. Keywords: literation, language, technology, children